Influence of Organizational Citizenship Behavior, Emotional Intelligence and Organizational Commitment on Employees' Work Ability - Riyanto P, Dita; Novitasari, Novitasari; Riska H, Adisty (Prosiding Seminar, 2022)
The purpose of this study was to determine and examine the effect of Organizational Citizenship Behavior (OCB), emotional intelligence and organizational commitment on employee work ability. This study uses a survey design of respondents to employees of PT. X, as many as 1500 people. The method used in sampling using purposive sampling based on certain criteria. The results of hypothesis testing in this study used multiple linear regression analysis. Hypothesis testing shows that organizational citizenship behavior, emotional intelligence and organizational commitment have a positive effect on the work ability of employees at PT. X City of Kediri. This study shows that employees who behave OCB indirectly affect the achievement of organizational tasks, because OCB behavior shown by employees will contribute to improving employee work abilities. Employees who have high emotional intelligence will certainly work better in accordance with organizational standards and achieve good work skills. And on the other hand, employees with a high commitment are needed to show optimal work abilities. So that they can contribute to an organization.